Correction: An in vitro method for inducing titan cells reveals novel features of yeast-to-titan switching in the human fungal pathogen Cryptococcus gattii. - Lamin Saidykhan; Joao Correia; Andrey Romanyuk; Anna F A Peacock; Guillaume E Desanti; Leanne Taylor-Smith; Maria Makarova; Elizabeth R Ballou; Robin C May (PLoS Pathogens, 2022)
[This corrects the article DOI: 10.1371/journal.ppat.1010321.].